C.R.E.A.R. : Centro de Residuos Enfocado en el Aprovechamiento de Residuos (2020)
A model project is proposed that manages to properly take advantage of all types of waste for the benefit of the community. Not only that integrates urban recycling with housing in a block of the UPZ of Las Nieves in the center of Bogota, but also improves certain deficit conditions. This block of the La Alameda neighbourhood is characterized by having several shops on the first floor, besides it already counts with many recycling centers and some high-rise developed housing buildings.Taking into account that there is already a consolidated population familiar with recycling activity, it is a suitable place to establish a treatment center that solves the conflicts presented by the current system. The new center will not only implement the existing dynamics for recyclable material, but will be able to handle the organic waste too, which represents the majority of the garbage generated in the area. However, there is as well a total lack of public space in the block and in general terms, in the whole sector. That is why it is proposed to develop a series of public spaces that get into the block and act as integration spaces and articulate existing uses with new ones: like a school-workshop, a communal hall and a daycare for children, which support the treatment center. The result will be a project where a treatment center and housing buildings coexist organized by the public space that will articulate the daily life of the neighbourhood, where it is understood that all garbage can be used to generate profits in order to meet the daily needs of cities. The organic waste will transform into resources such as gas and electricity, while recycable waste will be allowed to reincorporate in the industry that needs it or to turn into products for daily life.